Investigating the factors affecting human's weight perception in lifting objects with a power assist robot - Rahman, S. M. Mizanoor. (2013)
A power assist robot reduces perceived weight of objects lifted with it. However, root cause of reduced heaviness and factors affecting the heaviness are still unclear though the knowledge on the root cause/factors could be used to modulate human's feelings and the interactions between human and robot. This paper investigated the causes/factors behind the reduced heaviness. We adopted two strategies for this. Firstly, we included weight perception in robot dynamics (and control) in such a way that the mass parameter of the inertial force was considered different from that of the gravitational force because the perceived weight is different from the actual weight. Secondly, we compared weight perception, load forces and motions for power-assisted manipulation to that for manual manipulation and identified some clues regarding the causes/factors of reduced heaviness. We found that perceived weight, load force and its rate, velocity and acceleration for power-assisted objects were lower than that for manually lifted objects. We observed time delays in position sensing, force sensing, servomotor etc. for the power-assisted objects, however, the delays were almost absent for the manually lifted objects. We argued that the delays were the root cause of reduced heaviness and the elements of the system contributing to the delays were the factors affecting the perceived heaviness. To cross-check it, we increased time constant of the servomotor and found that the increased time constant reduced perceived weight. The findings may be used to develop power assist robots for manipulating heavy objects in industries that may help improve/modulate interactions between robots and users.